Photovoltaics and the solar rebound: Evidence for Germany - Manuel Frondel; Kathrin Kaestner; Stephan Sommer; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Recent research suggests that households increase their electricity consumption in the aftermath of installing photovoltaic (PV) panels, a behavioral change commonly referred to as the solar rebound. Drawing on panel data originating from the German Residential Energy Consumption Survey (GRECS), we employ panel estimation methods and the dynamic system estimator developed by Blundell and Bond (1998) to investigate the existence of a solar rebound effect, thereby accounting for simultaneity and endogeneity issues relating to PV installation and the electricity price. Our empirical results suggest that PV panel adoption of households does not change the amount of electricity taken from the grid. As we derive theoretically, this outcome implies a solar rebound that is bounded from above by about 50%, while back-of-the-envelope calculations provide us with a lower bound of 12% and an average solar rebound of 35%.
Keywords: C23; H10; Q41; 330; Feed-in tariffs; GMM system estimator; German Residential Energy Consumption Survey (GRECS)